Induction of ovulation with letrozole in women with polycystic ovary syndrome - G E Chernukha; E K Kaprina; A A Naidukova (IP Berlin A.V., 2017)
The aim of the study was to evaluate the effectiveness of the use of letrozole as an inducer of ovulation in women with polycystic ovary syndrome (PCOS) and anovulatory infertility and to determine possible clinical and laboratory predictors of the effect of therapy. Materials and methods: 61 women with anovulatory infertility and PCOS (mean age 28.5 ± 3.3 years, mean body mass index - BMI 21.8 ± 2.7 kg / m2) were included in the study. In order to induce ovulation, the patient received letrozole at a dose of 2.5-5 mg / day from day 3 to 7 of the menstrual cycle under the control of folliculometry, ultrasound m / pelvis on the 20-24 day cycle and the level of progesterone in the blood. Results: the frequency of ovulation per cycle was 77.2% (146/189), 98.4% for women, 24.9% for conception (47/189), 77% for women (47/61) , in 6 (12.8%) women the pregnancy was biochemical, in 1 (2.1%) ectopic, multiple pregnancy took place in 2 (5%) women with progressive uterine pregnancy, spontaneous abortion in the period up to 12 weeks of gestation occurred in 5 (12.5%) women, there was no case of ovarian hyperstimulation syndrome or other side effects. Comparative analysis revealed higher levels of BMI, the percentage of total adipose tissue by densitometry, and the number of antral follicles in the volume of the ovaries in the group with no pregnancy. Conclusion: letrozole is an effective medication for induction of ovulation and pregnancy in the treatment of infertility in patients with PCOS, characterized by good tolerability, low risk of multiple pregnancies and the absence of cases of ovarian hyperstimulation syndrome.